Physiochemical Characteristic and Biological Activity of the Clove (Syzygium aromaticum) Bud Oil - Abdel-Rahim, Awad M.; Osman, Samahir H.; A. Ali, Mai (Gezira Journal of Engineering and Applied Sciences, 2018)
The present study was investigating the physiochemical and the biological activity of the Clove bud oil against the fungus ( A. niger) and two bacteria ( E. coli and Staph. aurues ). The inhibition zone plate method was used for bacterial test, while the mycelia weights and radial growth methods were used for the fungal study. The A.O.S. official methods were used to determine the physiochemical properties. The studies on the physiochemical characteristics of the Clove bud oil proved that the acid value was (3.86), the saponification value was (38.27),the peroxide value was (3.83), the specific gravity was (1.043), the  reflective index was (1.525), the iodine value was (182.43), and the free fatty acid was (1.94). The results of the antimicrobial tests showed that  the  Clove bud oil gave a complete inhibition of the radial growth of the fungus ( A. niger) at its higher concentration and a high reduction percent at its lower concentrations. However, the mycelial fresh and dry weights of the fungus A. niger were completely inhibited by the Clove bud oil at its higher concentration, and clearly reduced at its lower concentrations. The inhibition zone of growth of both bacteria was larger than that of the control treatment. Clove bud oil showed clear inhibition zone when used against Staph. aurues compared to its use against E. coli. Many studies have reported that oils of different herbs and spices can yield medicinal compounds. Spices and herbs have been used for thousand of years by man in traditional medicine. However, more physiochemical characterizations need to be done and the antifungal and the antibacterial properties should be verified in any further studies on the Clove bud oil.